Beta Masih Takut: The Story of Forgiveness and Intergroup Anxiety from Post-Conflict Survivors - Mashuri, Muhammad Fath; Bono, Suzanna Awang; Hi.Ishak, Windasari (Faculty of Psychology, Universitas Gadjah Mada, 2024)
The prolonged conflict in the Moluccas from 1999 to 2003 continues to induce anxiety today, particularly among survivors. Fear is centered on affective aspects, such as the onset of anxiety and worry, leading to avoidance of other religious groups within their in-group. This is referred to as intergroup anxiety. Based on the results of a literature review, one of the factors that can influence the reduction of intergroup anxiety among post-conflict survivors is forgiveness. The aim of this study was to investigate the impact of forgiveness on intergroup anxiety. This study is a quantitative research project. Participants in this study were survivors of the Moluccas conflict, totaling 165 respondents who were selected using snowball sampling techniques. The study utilized the TRIM (Transgression Related Interpersonal Motivation Inventory) instrument and the intergroup anxiety scale. The data were analyzed using a simple linear regression test, resulting in a p-value of 0.731 (p > 0.05). These results indicate that forgiveness does not necessarily alleviate intergroup anxiety. There was no observed effect of forgiveness on intergroup anxiety among post-conflict survivors of the Moluccas. Demographic variables, such as religion and the impacts of conflict, also did not influence or differentiate the emergence of anxiety between groups.